2x+x+5+3x-6=6x-1
Cross-multiplying gives: (x + 3)(3 - 2x) = (3x + 1)(2x - 1) ie -2x2 - 3x + 9 = 6x2 - x - 1 add 2x2 to each side: -3x + 9 = 8x2 - x - 1 add 3x to each side: 9 = 8x2 + 2x - 1 subtract 9 from each side: 8x2 + 2x - 10 = 0 divide by 2: 4x2 + x - 5 = 0 Factors are: (4x + 5)(x - 1) x = -1.25 or 1
(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4
12x2 + 7x + 1 = 12x2 + 3x + 4x + 1 = 3x*(4x + 1) + 1*(4x + 1) = (4x + 1)*(3x + 1)
3x+x=4x. The 3x is just an easier way of stating x+x+x, and then you would just count the x's up like normal to create a total. You can also do this with larger numbers. For example, if you have 100x+500x, you would still add the numbers together to create a total of 600x. As long as the variables (x, in this case) are the same in the numbers you're adding (i.e., you can't add 3x+y together) you can just add the numbers to create your total.
3x + 4y + 10 + 12x + y + 1 First, combine like factors: 3x +12x + 4y + y +10 + 1 Add them (or subtract) as necessary: 15x + 5y + 11
I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?
9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2
3x + 11
If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)
2x2 + 3x + 1 = (x + 1)(2x + 1)
-3x + 1
(-3x - 1)(3x - 7)
If: 3x+5 = 4x+1 Then: x = 4
5x-3x+x+8 = 2x+1+x+x 3x+8 = 4x+1 3x-4x = 1-8 -x = -7 x=7 Hope that helps.
y = 3X - 1
y = 3x + 1